In‐hospital mortality in SARS‐CoV‐2 stratified by gamma‐glutamyl transferase levels. Issue 4 (9th March 2022) - Alroomi, Moudhi; Rajan, Rajesh; Alsaber, Ahmad; Pan, Jiazhu; Abdullah, Mohammed; Abdelnaby, Hassan; Aboelhassan, Wael; AlNasrallah, Noor; Al‐Bader, Bader; Malhas, Haya; Ramadhan, Maryam; Hussein, Soumoud; et al.
Abstract: Background: This study investigates in‐hospital mortality amongst patients with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and its relation to serum levels of gamma‐glutamyl transferase (GGT). Methods: Patients were stratified according to serum levels of gamma‐glutamyl transferase (GGT) (GGT<50 IU/L or GGT≥50 IU/L). Results: A total of 802 participants were considered, amongst whom 486 had GGT<50 IU/L and a mean age of 48.1 (16.5) years, whilst 316 had GGT≥50 IU/L and a mean age of 53.8 (14.7) years. The chief sources of SARS‐CoV‐2 transmission were contact (366, 45.7%) and community (320, 40%). Most patients with GGT≥50 IU/L had either pneumonia (247, 78.2%) or acute respiratory distress syndrome (ARDS) (85, 26.9%), whilst those with GGT<50 IU/L had hypertension (141, 29%) or diabetes mellitus (DM) (147, 30.2%). Mortality was higher amongst patients with GGT≥50 IU/L (54, 17.1%) than amongst those with GGT<50 IU/L (29, 5.9%). More patients with GGT≥50 required high (83, 27.6%) or low (104, 34.6%) levels of oxygen, whereas most of those with GGT<50 had no requirement of oxygen (306, 71.2%). Multivariable logistic regression analysis indicated that GGT≥50 IU/L (odds ratio [OR]: 2.02, 95% confidence interval [CI]: 1.20–3.45, p =0.009), age (OR: 1.05, 95% CI: 1.03–1.07, p <0.001), hypertension (OR: 2.06, 95% CI: 1.19–3.63, p =0.011), methylprednisolone (OR: 2.96, 95% CI: 1.74–5.01, p <0.001) and fever (OR: 2.03, 95% CI: 1.15–3.68, p =0.016) were significant predictors of all‐cause cumulative mortality. A Cox proportional hazards regression model (B = −0.68, SE =0.24, HR =0.51, p = 0.004) showed that patients with GGT<50 IU/L had a 0.51‐times lower risk of all‐cause cumulative mortality than patients with GGT≥50 IU/L. Conclusion: Higher levels of serum GGT were found to be an independent predictor of in‐hospital mortality. Abstract : Kaplan–Meier survival plot of mortality according to GGT levels in patients with coronavirus disease [COVID‐19]. X‐axis: Days since admission.